Cost‐effectiveness of possible future smoking cessation strategies in Hungary: results from the EQUIPTMOD. (25th January 2018) - Németh, Bertalan; Józwiak‐Hagymásy, Judit; Kovács, Gábor; Kovács, Attila; Demjén, Tibor; Huber, Manuel B.; Cheung, Kei‐Long; Coyle, Kathryn; Lester‐George, Adam; Pokhrel, Subhash; Vokó, Zoltán
Abstract: Aims: To evaluate potential health and economic returns from implementing smoking cessation interventions in Hungary. Methods: The EQUIPTMOD, a Markov‐based economic model, was used to assess the cost‐effectiveness of three implementation scenarios: (a) introducing a social marketing campaign; (b) doubling the reach of existing group‐based behavioural support therapies and proactive telephone support; and (c) a combination of the two scenarios. All three scenarios were compared with current practice. The scenarios were chosen as feasible options available for Hungary based on the outcome of interviews with local stakeholders. Life‐time costs and quality‐adjusted life years (QALYs) were calculated from a health‐care perspective. The analyses used various return on investment (ROI) estimates, including incremental cost‐effectiveness ratios (ICERs), to compare the scenarios. Probabilistic sensitivity analyses assessed the extent to which the estimated mean ICERs were sensitive to the model input values. Results: Introducing a social marketing campaign resulted in an increase of 0.3014 additional quitters per 1 000 smokers, translating to health‐care cost‐savings of €0.6495 per smoker compared with current practice. When the value of QALY gains was considered, cost‐savings increased to €14.1598 per smoker. Doubling the reach of existing group‐based behavioural support therapies and proactive telephone support resulted in health‐care savings of €0.2539 per smoker (€3.9620 with the value of QALY gains), compared with current practice. The respective figures for the combined scenario were €0.8960 and €18.0062. Results were sensitive to model input values. Conclusions: According to the EQUIPTMOD modelling tool, it would be cost‐effective for the Hungarian authorities introduce a social marketing campaign and double the reach of existing group‐based behavioural support therapies and proactive telephone support. Such policies would more than pay for themselves in the long term.